Difference between revisions of "1994 AHSME Problems/Problem 1"

m (LaTeX is FAT)
(Solution)
Line 8: Line 8:
 
Note that <math>a^x\times a^y=a^{x+y}</math>. So <math>4^4\cdot 4^9=4^{13}</math> and <math>9^4\cdot 9^9=9^{13}</math>. Therefore, <math>4^{13}\cdot 9^{13}=(4\cdot 9)^{13}=\boxed{\textbf{(C)}\ 36^{13}}</math>.
 
Note that <math>a^x\times a^y=a^{x+y}</math>. So <math>4^4\cdot 4^9=4^{13}</math> and <math>9^4\cdot 9^9=9^{13}</math>. Therefore, <math>4^{13}\cdot 9^{13}=(4\cdot 9)^{13}=\boxed{\textbf{(C)}\ 36^{13}}</math>.
  
--Solution by [[User:TheMaskedMagician|TheMaskedMagician]] 23:04, 27 June 2014 (EDT)
+
--Solution by [http://www.artofproblemsolving.com/Forum/memberlist.php?mode=viewprofile&u=200685 TheMaskedMagician]

Revision as of 22:06, 27 June 2014

Problem

$4^4 \cdot 9^4 \cdot 4^9 \cdot 9^9=$

$\textbf{(A)}\ 13^{13} \qquad\textbf{(B)}\ 13^{36} \qquad\textbf{(C)}\ 36^{13} \qquad\textbf{(D)}\ 36^{36} \qquad\textbf{(E)}\ 1296^{26}$

Solution

Note that $a^x\times a^y=a^{x+y}$. So $4^4\cdot 4^9=4^{13}$ and $9^4\cdot 9^9=9^{13}$. Therefore, $4^{13}\cdot 9^{13}=(4\cdot 9)^{13}=\boxed{\textbf{(C)}\ 36^{13}}$.

--Solution by TheMaskedMagician

Invalid username
Login to AoPS